Analysis of the use of solid fuel for domestic use (Research, Society and Development, 2022)
This work aimed to ascertain the quality of solid fuels for domestic consumption. The tests were carried out from six types of materials of tree origin of the genus Eucalyptus, being firewood, charcoal and four types of briquettes of charcoal. Analyzes of moisture, proximate analysis, densities, thermal analysis and by scanning electron microscopy (SEM) were performed. The results obtained from these analyzes were similar to those in the literature. Treatments from charcoal briquettes showed higher energy density than the others, of all treatments, the T4 was the one that presented better energy capacity to the other treatments without correlation with the costs